"It All Starts with Family": Mechanisms of Intergenerational Poverty in the Veenkoloniën, the Netherlands. Issue 6 (19th September 2022) - Visser, Sanne Siete; Edzes, Arjen; Merx, Erik; van Lanen, Sander
ABSTRACT: Mechanisms that drive the intergenerational transmission of poverty have been studied widely, but to understand how these mechanisms are at work in real life we require studies on perspectives of families who themselves are living in poverty. In this study, we combine the perspectives of multiple generations of family households in a rural area in the Netherlands. We want to understand from their own perspective what prevents these families from escaping poverty. Twenty-three family households participated in intergenerational interviews. Results show that recurrent mechanisms were often perceived to relate to rearing practices, norm-setting and geographical mechanisms (immobility and perceived place-based stigma). Family habitus structures the mechanisms that prolong and perpetuate poverty.